Thermal flow characteristics and the evolution of laser absorption in laser powder bed fusion of Cu-Cr-Zr alloy. (15th February 2022) - Ren, Zhihao; Fu, Guang; Zhang, David Z.; Zhang, Kaifei; Zhao, Miao
Highlights: A new loading pattern of heat source is proposed to restrict the artificial high temperature in LPBF simulation. A measured absorptivity by calorimetric experiments significantly enhances simulation fidelity. The distinctions of melt pool dynamics due to huge thermal conductivity is clarified. Abstract: The ultra-high transience and complexity of the LPBF process brings critical challenges to understanding the underlying physics behind the defect formation, and mathematical modeling of the melt pool dynamics in LPBF is being a good method to overcome this issue. Since the laser heating is central to the LPBF process, it is vital to pay more attention to how to define the laser heat source in simulation. This study focuses on the "top free surface" heat source model that is widely used in existing literatures, of which two aspects of deficiencies are modified. On the one hand, the loading pattern of heat source at the interface is optimized by a proposed scattered heat source (SHS) model. The results show that the SHS model has an apparent advantage of less generation of artificial high temperature and better energy convergence. On the other hand, a calorimetric measurement is adopted to obtain the practical effective laser absorptivity under different process parameters. With implantation of measured absorptivity, the simulation fidelity compared to experiments is significantly enhanced in terms the track width and depth, and the absorptivity uncertainty derived from existing literatures on modeling copper alloy is well solved. Next, the physics behind the variation of effective absorptivity with scan speed is studied. Then, the characteristics of Cu-Cr-Zr alloy in LPBF induced by the huge thermal conductivity is identified by comparing with the case of commonly LPBF-used material (stainless steel 316 L). Finally, the influence of scan speed on the resultant track morphology and keyhole-induced porosity evolution is discussed. Graphical abstract: Image, graphical abstract